2018
DOI: 10.1108/jgr-06-2017-0039
|View full text |Cite
|
Sign up to set email alerts
|

Environmental responsibility: millennial values and cultural dimensions

Abstract: Purpose This study aims to examine how students in business colleges across three countries, the United States, India and China, interpret environmental sustainability. This study also explores where students from different cultures believe responsibility lies in caring for the environment and how these beliefs represent their cultural and millennial values. The purpose of this study, then, is to investigate millennial business students’ perspectives toward the environment across the three countries holding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 14 publications
2
15
1
Order By: Relevance
“…All three dimensions of sustainability (economic, socio-cultural, and ecological) have been found to have a positive effect on SMO. In this regard, these results extend findings of previous studies, which either did not specifically address the relationship between selftranscendence values and the economic dimension of sustainability (Hanson-Rasmussen and Lauver, 2018) or provided mixed results concerning the association of these constructs (Wang and Juslin, 2011;Kausch, 2013). We show that having self-transcendence values does not necessarily contradict conceptualizing aspects such as economic growth, efficiency, and technological progress as integral parts of sustainability.…”
Section: Resultssupporting
confidence: 86%
“…All three dimensions of sustainability (economic, socio-cultural, and ecological) have been found to have a positive effect on SMO. In this regard, these results extend findings of previous studies, which either did not specifically address the relationship between selftranscendence values and the economic dimension of sustainability (Hanson-Rasmussen and Lauver, 2018) or provided mixed results concerning the association of these constructs (Wang and Juslin, 2011;Kausch, 2013). We show that having self-transcendence values does not necessarily contradict conceptualizing aspects such as economic growth, efficiency, and technological progress as integral parts of sustainability.…”
Section: Resultssupporting
confidence: 86%
“…Environmental responsibility refers to "a state in which a person expresses an intention to take action directed toward remediation of environmental problems-acting not as an individual consumer with his or her own economic interests, but through a citizen-consumer concept of societal-environmental well-being" [48]. Prior study has shown that consumers' environmental responsibility is closely related to environmental education, which varies across different nationals and cultures [47,49]. The positive relationship between consumers' environmental responsibility and green consumption behavior has been examined in some different countries.…”
Section: Environmental Responsibility and Green Consumption Intentionmentioning
confidence: 99%
“…As Millennials are aware of the problems concerning the ecosystem, even if few young people have real in-depth knowledge on the subject, it is logical to expect that they adopt new behaviours that support sustainable development (Ivanova et al 2019). Many studies identify a greater propensity to sustainable buying for Millennials than previous generations (Fischer et al 2017;Hanson-Rasmussen and Lauver 2018). The results of the research by Kanchanapibul et al (2014) show that there is a good relationship between the Millennials and the world of ecology.…”
Section: Millennials Consumption and Green Consumption Featuresmentioning
confidence: 99%
“…Among consumers, Millennials are regularly considered the ones driving the sustainable movement with their lifestyle and behavioural changes (Sheahan 2005;Smith 2011;Hanson-Rasmussen and Lauver 2018). Therefore, they are also referred to as the "Green Generation".…”
Section: Introductionmentioning
confidence: 99%